2011
DOI: 10.3999/jscpt.42.11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Eltrombopag in Healthy Japanese Males

Abstract: The pharmacokinetics and pharmacodynamics of eltrombopag, a thrombopoietin receptor agonist developed for idiopathic thrombocytopenic purpura, were investigated in healthy Japanese adult males after single and repeat doses of eltrombopag in two clinical studies. In the first study, subjects received a single oral dose of eltrombopag tablets at 30, 50, 75 and 100 mg and placebo in the fasted state. In the second study, each subject received single and once daily for 10 days repeat doses of eltrombopag(25, 50 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…An inter-ethnic difference in the pharmacokinetics of eltrombopag has been observed between East Asian and non-Asian patients with ITP, as well as between East Asian and non-Asian healthy volunteers [21]; in our study, the AUC 0– τ in Japanese patients receiving 37.5 mg of eltrombopag once daily was estimated to be 236 μg h/mL, which is similar to that seen in non-East Asian patients with CLD receiving 75 mg once daily in a previous study [26]. Although the mechanisms underlying an inter-ethnic difference in the pharmacokinetics of eltrombopag remain unclear, a common difference between East Asian and Caucasian ethnic groups is body weight [27]. Because the clearance of eltrombopag increased with body weight [21] and because the body weight of East Asian patients is lower than that of Caucasian patients in general, body weight differences could account for the differences in serum levels of eltrombopag seen between the two groups.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…An inter-ethnic difference in the pharmacokinetics of eltrombopag has been observed between East Asian and non-Asian patients with ITP, as well as between East Asian and non-Asian healthy volunteers [21]; in our study, the AUC 0– τ in Japanese patients receiving 37.5 mg of eltrombopag once daily was estimated to be 236 μg h/mL, which is similar to that seen in non-East Asian patients with CLD receiving 75 mg once daily in a previous study [26]. Although the mechanisms underlying an inter-ethnic difference in the pharmacokinetics of eltrombopag remain unclear, a common difference between East Asian and Caucasian ethnic groups is body weight [27]. Because the clearance of eltrombopag increased with body weight [21] and because the body weight of East Asian patients is lower than that of Caucasian patients in general, body weight differences could account for the differences in serum levels of eltrombopag seen between the two groups.…”
Section: Discussionmentioning
confidence: 63%
“…A pharmacogenetic study has also been performed to investigate a relationship between gene polymorphisms and inter-ethnic differences; however, the responsible polymorphism has not been identified (data not shown). Eltrombopag is a substrate of several drug-metabolizing enzymes, including cytochrome P450 (CYP) 1A2, CYP2C8, uridine diphosphate-glucuronosyltransferase (UGT) 1A1, and UGT1A3, and the agent is also a substrate of breast cancer resistance protein [27]. Because the activities of these enzymes are known to have inter-ethnic differences [28, 29], it is possible that multiple factors, including genetic differences in metabolizing enzymes and transporters, may be involved in the observed difference [27].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy volunteers, eltrombopag dose-dependently increased platelet counts, which returned to baseline after the drug was discontinued, and, unlike thrombopoietin, appeared to have no effect on platelet function, such as aggregation or activation [9][10][11]. In adults with severe aplastic anaemia, eltrombopag therapy for 12 weeks did not affect leukocyte telomere length, modify any T cell subsets or change the elevated thrombopoietin levels present at baseline [7].…”
Section: How Does Eltrombopag Work?mentioning
confidence: 77%
“…It is suggested that low-dose 25 mg once-daily eltrombopag therapy suffices in most patients of Asian origin (compared with in Caucasians, who usually require double this dose) 90. The underlying mechanism accounting for the observed interethnic difference in the pharmacokinetics of eltrombopag is not clear; nonetheless, the most plausible explanation appears to be the difference in the body weight (less in East Asian population compared with the general Caucasian population) 91. Since the clearance of eltrombopag increases with increase in body weight,92 heavy subjects need higher doses to produce an identical therapeutic effect.…”
Section: Treatmentmentioning
confidence: 99%
“…Since the clearance of eltrombopag increases with increase in body weight,92 heavy subjects need higher doses to produce an identical therapeutic effect. Another possible explanation is the known interethnic differences92,93 in the levels of activities of different drug metabolizing enzymes involved in eltrombopag metabolism (eg, CYP1A2, CYP2C8, UGT1A1, and UGT1A3) 91. The predominant route of eltrombopag excretion is via feces (59%) followed by urine (31%).…”
Section: Treatmentmentioning
confidence: 99%